Physiological differences between world-class and national-level ski mountaineers - Savoldelli, A.; Fornasiero, A.; Callovini, A.; Decet, M.; Schena, F.; Pellegrini, B.; Bortolan, L. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Ski Mountaineering requires both pronounced physiological capacity when skiing uphill and remarkable downhill skiing technique (Bortolan, 2022). Even if for XC-skiing several studies have demonstrated that male world-class skiers are among the endurance athletes with the highest VO2max (Losnegard, 2019), less is known about ski mountaineers and the difference between performance levels of athletes.